INFLUENCE OF USING MACROMEDIA FLASHCOMBINED WITH LKS OF SCIENCE PROCESS SKILLS CLASS X SMA N 2 METRO - Erni Mariana (RETEL Journal (Journal on Publication of The Research on Teaching and Language), 2017)
Based on the pre-survey conducted that in teachingusually teachersuse the lecture method. There aremany students with low science process skills and only a few students with high science process skills. The purpose of this study was to determine whether or not the influence of macromedia flash combined with LKS on the science process skills of class X students of SMA N 2 Metro. This study techniqueused a cluster random sampling technique, because class X consisted of seven classes, so two classes were taken. randomly used as samples, class X4 as theclass experimentaland X2 as the control class. Theinstruments used in this study were questionnaire sheets, observation sheets, and tests. The analysis in this study used the two average similarity test and the two average difference test. Based on the test results of two average difference data obtained tdaf (? = 5%) = 1.67 and thit = 3.02 to thit>tdafwhich means that the average skill pross science experiment class students is higher than the average science process skills in the control class there is an influence of the use of macromedia flash combined with LKS on the science process skills of class X students of SMA N 2 Metro. Based on the description above it can be suggested that teachers should be able to use learning media in the form of macromedia flash combined with LKS. Keywords: Macromedia Flash, LKS, and Science Process Skills.